Customer Satisfaction towards Service in the Tourism Business Case Study: Your Friends Travel Company, Phitsanulok Province - ธรรมพัฒนากูล, มนตรี; ทวินันท์, กาญจนา; ประสงค์, เพ็ญนภา; ผาสิงห์, ฉัตรพล (Business Administration and Management Journal Review, 2019)
The purposes of this research were 1) to study customer’s satisfaction towards services in the tourism business 2) to compare thecustomer’s satisfaction level towards services in the tourism business, a case study of Your Friends Travel, Phitsanulok Province. It was the quantitative research. The collected data by questionnaire from 133 consumers of Your Friends Travel at Phitsanulok Province. The data were analyzed applying by Percentage, Mean, Standard Deviation, Independent Samples t-test, One way ANOVA. The results of the study found that overall of consumers at Your Friends Travel were in the highest level satisfaction. When considering their satisfaction classified by the Service Quality elements, it was found that The level of satisfaction is also at the highest level in all aspects: empathy, reliability, responsiveness, reliability and tangibility, respectively. 2) Overall, no significant difference was found in consumers tourism business satisfaction level with different personal factors at a statistical significance level of 0.05.